Event-triggered output feedback tracking control for uncertain strict-feedback nonlinear systems subject to input saturation - Li, Hanfeng; Li, Min (Journal of the Franklin Institute, 2025)
This paper presents a novel event-triggered output feedback control method to achieve the tracking performance for uncertain strict-feedback nonlinear systems with input saturation. Unlike most existing tracking control strategies that are built upon the backstepping design method, the proposed control scheme is derived from an auxiliary system about the saturation error and the hyperbolic tangent function, together with the dynamic scaling transformations. Based on the designed event-triggered controller, the tracking error converges to the neighborhood of a pre-specified interval. Moreover, all closed-loop signals are bounded despite appearing as saturated phenomenon. By introducing an auxiliary system and constructing a new dynamic gain function, the boundedness of the saturation error can be guaranteed through the Lyapunov analysis, and the common assumption about the boundedness of saturation error can be avoided effectively. A practical example is provided to authenticate the usefulness and benefit of the proposed control method.